Adventitial lymphatics of internal carotid artery in healthy and atherosclerotic vessels. - Ryszard Andrzejak; Piotr Ziółkowski; Dariusz Patrzałek; Marzena Podhorska; Piotr Dziegiel; Dariusz Janczak; Katarzyna Drozdz; Andrzej Szuba (Folia Histochemica et Cytobiologica, 2009)
OBJECTIVES Presence of lymphatics in adventitia of major arteries remains controversial. Presence of lymphatics in adventitia of internal carotid artery was not documented and its relation to atherosclerosis was not studied. The aim of our study was to evaluate presence of lymphatic vessels in adventitia of internal carotid artery in healthy and atherosclerotic arteries. METHODS Fragments of arterial wall of internal carotid artery were obtained during the surgical eversion endarterectomy in 15 patients with internal carotid artery stenosis and 2 healthy organ donors. 21 arteries were studied. Patients age ranged from 56 to 77 years. Fragments of arterial wall were embeded in paraffin. Lymphatics of arterial adventitia were visualized with immunohistochemistry using LYVE-1 and anty-podoplanin antibodies. RESULTS The lymphatic vessels were visualized in adventitia of 20 carotid arteries. The serial sections have revealed that both LYVE-1 and podoplanin have identical specificity for lymphatic endothelium Number of lymphatics in adventitia significantly correlated with thickness of intima (p<0.046). CONCLUSIONS Lymphatics are present in adventitia of internal carotid artery. Number of adventitial lymphatics increases with severity of atherosclerosis measured as intimal thickness.